2019
DOI: 10.3390/pathogens9010014
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Effect of Clove Oil against Multidrug-Resistant Streptococcus suis Isolated from Human Patients and Slaughtered Pigs

Abstract: Streptococcus suis is a zoonotic pathogen that is currently considered an emerging multidrug-resistant (MDR). Increasing antibiotic resistance can lead to the unsuccessful treatment of S. suis infection. Recently, many investigations of medicinal plants were conducted for the treatment of infection as a result of the increase of antibiotic-resistant bacteria. The aims of this study were to determine the chemical composition of essential oil from Syzygium aromaticum (L.) Merr. & L.M. Perry and the antibacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Additionally, Shukri et al [42] revealed that the dietary cloves in vivo reduced the tissue damages in the livers, lens, and cardiac muscles in rats. Pharmacologically, clove oil is used in a wide range as an antiseptic in oral diseases and for the treatment of toothaches, allergy disorders, asthma, acne, scars, and rheumatoid arthritis, and it showed antispasmodic and acaricidal effects toward Dermatophagoides pteronyssinus and Dermatophagoides farina [43,44]. Moreover, the CEO has shown aphrodisiac, antipyretic, appetizer, hypnotic, anxiolytic, antiemetic, analgesic, decongestant, antimicrobial, antiepileptic, myorelaxant, anti-inflammatory, and expectorant properties as well as has a medicinal influence against trophic disorder [37,45].…”
Section: Biological/biochemical Properties Of S Aromaticummentioning
confidence: 99%
“…Additionally, Shukri et al [42] revealed that the dietary cloves in vivo reduced the tissue damages in the livers, lens, and cardiac muscles in rats. Pharmacologically, clove oil is used in a wide range as an antiseptic in oral diseases and for the treatment of toothaches, allergy disorders, asthma, acne, scars, and rheumatoid arthritis, and it showed antispasmodic and acaricidal effects toward Dermatophagoides pteronyssinus and Dermatophagoides farina [43,44]. Moreover, the CEO has shown aphrodisiac, antipyretic, appetizer, hypnotic, anxiolytic, antiemetic, analgesic, decongestant, antimicrobial, antiepileptic, myorelaxant, anti-inflammatory, and expectorant properties as well as has a medicinal influence against trophic disorder [37,45].…”
Section: Biological/biochemical Properties Of S Aromaticummentioning
confidence: 99%
“…The work of Libante et al [18] highlights the importance of reducing the prophylactic use of antimicrobials in livestock productions and the development of alternative control measures. In this regard, Wongsawan et al [19] explored the bactericidal effect of clove oil against S. suis in vitro. It was found that eugenol is the major active ingredient of clove oil and a promising alternative product for control of infectious diseases caused by S. suis.…”
mentioning
confidence: 99%
“…Earlier studies on essential oils reported antibacterial effects against Gram-negative bacterial strains causing urinary tract infections [ 41 ]. The anti-MRSA potential of clove oil has also been reported and has highlighted the need to explore bioactive constituents [ 42 ]. The phytochemicals present in clove bud oil are responsible for antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%